Large-Area Tunable Visible-to-Near-Infrared Luminescent Solar Concentrators - Correia, Sandra F. H.; Frias, Ana R.; Fu, Lianshe; Rondao, Raquel; Pecoraro, Edison [UNESP]; Ribeiro, Sidney J. L. [UNESP]; Andre, Paulo S.; Ferreira, Rute A. S.; Carlos, Luis D. (Wiley-Blackwell, 2018)
Luminescent solar concentrators (LSCs) appear as an intriguing way to cope with the limitation of the mismatch between the photovoltaic (PV) cells response and the solar spectrum, with the additional advantage of facilitating urban integration of photovoltaics. A new LSCs geometry based on triangular hollow-core plastic optical fibers (POFs) filled with organic-inorganic hybrid materials doped with Rhodamine 6G, Rhodamine 800, or an Europium beta-diketonate complex is presented. Large-area LSCs are built from POFs bundle structures, whose assembling is favored by the fiber triangular cross section that also maximizes the coverage of a PV cell surface compared with cylindrical POFs. Each bundle fiber behaves as an individual LSC absorbing UV/blue components of the solar spectrum and emitting visible/NIR radiation. The LSCs are characterized by optical conversion efficiency values up to eta(opt) approximate to 5.3%, among the largest values reported for single-layer LSCs. Moreover, the coupling between the LSCs to commercial Si PV cells yields maximum power conversion efficiency values of PCE approximate to 0.74%. The individual waveguiding features of each fiber in the bundle contribute to reduce the reabsorption, as lower performance values (eta(opt)approximate to 1.5%; PCE approximate to 0.09%) are estimated for a planar LSC with analogous surface collection area and light-harvesting absorbance.
Keywords: bundles; luminescent solar concentrators; organic-inorganic hybrids; visible and near infrared emission